KYOTO PROTOCOL 2ND COMMITMENT: Kerja Sama Clean Development Mechanism Australia-Ethiopia Dalam Energy Efficient Stove Program (EESP) Periode 2013-2020 - Mentari, (2021)
The shift from the use of human power to the use of machine power as a means of production has drastically changed the international world. This phenomenon led to what is known as the industrial revolution. This transition is marked by the massive use of engine power and lead to massive use of petroleum as result. In the end of this condition encourages the production of excessive greenhouse gas emissions. This problem opens a new chapter and challenge for the development of the international world, which is called climate change. His appearance then stole the attention of the international community and changed the world view that environmental issues can also be oriented to security issues. This issue became the beginning of the formation of joint initiatives, that aimed to overcoming climate change problem keep worsening, one of which is the Kyoto Protocol 2nd (Doha Amendment to the Kyoto Protocol) with its three GHG reduction mechanisms. Ethiopia and Australia are two countries that both have problems and interests in this issue, which ultimately led them to ratify this agreement. Through the CDM, one of the GHG reduction mechanisms of the Kyoto Protocol is the Energy Efficient Stove Program (ESSP) which runs for 10 years (2013-2022). In this paper, the author will focus on implementation in 2013-2020 to adjust to the validity period of the second period of the Kyoto Protocol. Behind this cooperation, the two countries take advantage of each other and fulfill their respective goals/interests, with this cooperation, Ethiopia can overcome the problem of releasing CO2 in their country and provide other benefits such as social and economic. Meanwhile, with this cooperation, Australia can maintain its existence and build a good image in the world. Through this research, the author wants to see how Australia's policy uses the Kyoto Protocol 2 as one of the venues where Australia can slip its interests and overcome the issue of climate change.